STUDY OF THE EFFECT OF CULTIVATION PATTERNS AND COFFEE FRUITS BORING PEST ATTACKS (CBF) ON THE PHYSICAL QUALITY AND EXPORT FEASIBILITY OF ARABICA COFFEE (Coffea arabica L.) IN NORTH TAPANULI DISTRICT - Flora Erika Simbolon; Nurhayati; Asmanizar (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
Arabica coffee is one of Indonesia's leading export commodities that is highly dependent on the physical quality of the beans and the accuracy of cultivation practices. This study aims to examine the effect of cultivation patterns and Coffee Berry Borer (PBKo) attacks on the physical quality and export feasibility of Arabica coffee in North Tapanuli Regency. The method used is a descriptive quantitative approach with field surveys, direct observation, and laboratory tests on coffee beans from 91 farmers assisted by PT Sumatera Specialty Coffee (SSC). Data were analyzed using descriptive statistics, multiple linear regression, and Pearson correlation. The results showed that good cultivation patterns significantly improved the physical quality of coffee, while PBKo attacks had a negative impact on export feasibility. It was found that selective harvesting techniques and integrated pest control significantly reduced the number of defective beans and increased the uniformity of bean size and color. These findings confirm that the integration of high-standard cultivation practices and effective pest management is needed to improve the competitiveness of Arabica coffee from North Tapanuli in the global market.